Internal structure of the action and acceptance questionnaire II (AAQ-II): evidence for a three-factor and bifactor model in two samples of university students - Daniel Núñez; César Villacura-Herrera; Javier Cubillos; Martín Donoso; Álvaro I. Langer (PeerJ, 2025)
Background Experiential avoidance (EA), defined as an inflexible behavioral pattern by which a person tries to avoid contact with private unpleasant situations, is considered a transdiagnostic variable associated with various psychopathological disorders. The Acceptance and Action Questionnaire II (AAQ-II) is a broadly used measure of EA. However, inconsistencies in the methods employed for examining its internal structure and the need for culturally validated measures in diverse populations highlight the need for further study. We conducted two studies in Spanish-speaking university students (nStudy1 = 829; nStudy2 = 830) to determine the validity and reliability of the AAQ-II. Methods In the first study, we examined the questionnaire through exploratory factor analysis (EFA). In the second study, we conducted confirmatory factor analysis (CFA) to examine how well these factor structures fit our data. Results We suggested a three-factor structure (namely: painful memories, emotional distress, and affective control), in contrast with the unidimensional model consistently reported in the literature. The three-factor model showed a better fit overall. Additionally, we tested a bifactor model to determine the feasibility of a general factor. Our results suggested that this general factor explained a high amount of the variance within the model when compared to the three independent factors. In terms of convergent validity, significant positive associations were found between EA and suicidal ideation, depressive and anxious symptoms, while negative associations were found with psychological well-being. The factor structures tested showed good internal consistency indices (ω = 0.853–0.918; α = 0.853–0.918). Discussion We discuss our results in terms of their methodological and practical implications for the use of the AAQ-II.